Olig2-dependent developmental fate switch of NG2 cells - Zhu, Xiaoqin (Company of Biologists, 2012)
NG2-expressing cells (NG2 cells or polydendrocytes) generate oligodendrocytes throughout the CNS and a subpopulation of protoplasmic astrocytes in the gray matter of the ventral forebrain. The mechanisms that regulate their oligodendrocyte or astrocyte fate and the degree to which they exhibit lineage plasticity in vivo have remained unclear. The basic helix-loop-helix transcription factor Olig2 is required for oligodendrocyte specification and differentiation. We have found that Olig2 expression is spontaneously downregulated in NG2 cells in the normal embryonic ventral forebrain as they differentiate into astrocytes. To further examine the role of Olig2 in NG2 cell fate determination, we used genetic fate mapping of NG2 cells in constitutive and tamoxifen-inducible Olig2 conditional knockout mice in which Olig2 was deleted specifically in NG2 cells. Constitutive deletion of Olig2 in NG2 cells in the neocortex and corpus callosum but not in ventral forebrain caused them to convert their fate into astrocytes, with a concomitant severe reduction in the number of oligodendrocytes and myelin. Deletion of Olig2 in NG2 cells in perinatal mice also resulted in astrocyte generation from neocortical NG2 cells. These observations indicate that the developmental fate of NG2 cells can be switched by altering a single transcription factor Olig2.